The Influence of Obesity on Bone Health in Post-COVID-19 Recovery- Single-Center Experience - Chaturvedi B; Debnath S; Bareth H; Raj P; Singh P; Singh M; Nathiya D; Tomar BS (International Journal of General Medicine, 2024)
Bhumi Chaturvedi,1 Sourav Debnath,1 Hemant Bareth,1 Preeti Raj,2 Pratima Singh,3 Mahaveer Singh,4 Deepak Nathiya,1,5,6 Balvir Singh Tomar5– 7 1Department of Pharmacy Practice, National Institute of Medical Sciences and Research, Jaipur, Rajasthan, India; 2School of Health Sciences, Faculty of Biology, Medicine and Health, University of Manchester, Manchester Academic Health Science Centre, Manchester, UK; 3Public Health and Preventive Medicine, University of Alberta, Edmonton, AB, Canada; 4Department of Endocrinology, National Institute of Medical Sciences and Research, Jaipur, Rajasthan, India; 5Department of Clinical Studies, Fourth Hospital of Yulin (Xingyuan), Yulin, Shaanxi, People’s Republic of China; 6Department of Clinical Sciences, Shenmu Hospital, Shenmu, Shaanxi, People’s Republic of China; 7Institute of Pediatric Gastroenterology and Hepatology, National Institute of Medical Sciences and Research, Jaipur, Rajasthan, IndiaCorrespondence: Mahaveer Singh, Department of Endocrinology, National Institute of Medical Sciences and Research, Nims University, Jaipur, Rajasthan, India, Email drms.mamcmed@gmail.comIntroduction: The ongoing repercussions of the COVID-19 pandemic include potentially deleterious impacts on bone health.Aim: This research aimed to ascertain the effects of COVID-19 on the bone health of obese and non-obese Indian individuals.Methods: We executed a case-control study enrolling individuals who recovered from COVID-19. Participants were stratified into obese and non-obese groups based on their BMI. Comprehensive assessments encompassed anthropometric evaluations, laboratory tests, and bone mineral density (BMD) measurements using dual-energy X-ray absorptiometry (DEXA).Results: From April to July 2022, we enrolled obese (n = 27, mean BMI = 30.54 ± 4.51 kg/m 2) and non-obese (n = 23, mean BMI = 21.97 ± 2.20 kg/m 2) individuals. The cohort’s average age was 36.08 ± 15.81 years, with a male-to-female ratio of 1.6:1. There was a difference in BMD, especially at the total hip, between the two groups. BMD at the spine (L1-L4), the neck of the femur, and ultra-distal radius were consistent across both groups. Weight exhibited a significant positive correlation with BMD at L1-L4 (r = 0.40, p = 0.003) and the left femur total (r = 0.27, p = 0.001). Haemoglobin levels were lower in the obese group compared to their non-obese counterparts (12.3 ± 2.0 vs 13.6 ± 1.9, p = 0.01). Multivariate analysis underscored weight as a crucial predictor for BMD at the spine (L1-L4, p = 0.003) and total hip (p = 0.001).Conclusion: Even with advanced age, obese post-COVID-19 individuals demonstrate a higher bone mineral density (BMD) at the hip than non-obese subjects.Keywords: COVID-19, obesity, bone mineral density, osteopenia, fracture risk